Homo prospectus - Seligman, Martin E. P. (Oxford University Press, 2016)
In this remarkable convergence of research in philosophy, statistics, decision theory, psychology, and neuroscience, Homo Prospectus shows how human prospection fundamentally reshapes our understanding of key cognitive processes, thereby improving individual and social functioning. It aims to galvanize interest in this new science from scholars in psychology, neuroscience, and philosophy, as well as an educated public curious about what makes humanity what it is.